2016
DOI: 10.1177/0255761415619390
|View full text |Cite
|
Sign up to set email alerts
|

Musical preference and music education: Musical preferences of Turkish university students and their levels in genre identification

Abstract: The aim of this study was to investigate if there is any relationship between musical preference, genre identification and frequency of listening to music genres, and whether musical training and gender played a role in these factors. A total of 205 college music and non-music majors recorded their preference for 13 music excerpts in popular, non-popular and Turkish Music genres. Results suggested that students' musical preference, frequency of listening to music genres and their levels of accuracy in genre id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…Colley (2008) confirmed the greater liking of heavier contemporary music among men while women preferred chart pop music. Gurgen (2016) found that Turkish female students preferred jazz, latin, reggae and western music, while male students preferred the excerpts of rock and metal music.…”
Section: Discussionmentioning
confidence: 98%
“…Colley (2008) confirmed the greater liking of heavier contemporary music among men while women preferred chart pop music. Gurgen (2016) found that Turkish female students preferred jazz, latin, reggae and western music, while male students preferred the excerpts of rock and metal music.…”
Section: Discussionmentioning
confidence: 98%
“…In combination with its evanescent nature it is sometimes difficult to grasp the music's meaning and to translate one's understanding of the music into adequate musical intentions that shape musical interaction. Therefore, music teachers often rely on verbal explanations, using for example structural analysis and metaphors (Meissner 2016;Schippers 2006). And yet, musical interaction is at the same time a very physical experience (Bresler 2004;Leman 2007;Leman and Nijs 2016).…”
Section: Making the Abstract Concretementioning
confidence: 99%
“…Music listening frequency scale developed by Gürgen (2015) was used to determine the musical genres listened by students. The question "what kind of music do you listen?"…”
Section: Data Collection Toolsmentioning
confidence: 99%